Recent Advances in Drumstick (Moringa oleifera) Leaves Bioactive Compounds: Composition, Health Beneﬁts, Bioaccessibility, and Dietary Applications - Kashyap, P. (2022)
Based on the availability of many nutrients, Moringa oleifera tree leaves have been widely employed as nutrients and nutraceuticals in recent years. The leaves contain a small amount of anti-nutritional factors and are abundant in innumerable bioactive compounds. Recently, in several in vivo and in vitro investigations, moringa leaves’ bioactive components and functionality are highlighted. Moringa leaves provide several health advantages, including anti-diabetic, antibacterial, anti-cancer, and anti-inflammatory properties. The high content of phytochemicals, carotenoids, and glucosinolates is responsible for the majority of these activities as reported in the literature. Furthermore, there is growing interest in using moringa as a value-added ingredient in the development of functional foods. Despite substantial study into identifying and measuring these beneficial components from moringa leaves, bioaccessibility and bioavailability studies are lacking. This review emphasizes recent scientific evidence on the dietary and bioactive profiles of moringa leaves, bioavailability, health benefits, and applications in various food products. This study highlights new scientific data on the moringa leaves containing nutrient and bioactive profiles, bioavailability, health benefits, and uses in various food items. Moringa has been extensively used as a health-promoting food additive because of its potent protection against various diseases and the widespread presence of environmental toxins. More research is needed for utilization as well as to study medicinal effects and bioaccesibility of these leaves for development of various drugs and functional foods.